2011
DOI: 10.1155/2011/865435
|View full text |Cite
|
Sign up to set email alerts
|

15,16‐Dihydrotanshinone I, a Compound of Salvia miltiorrhiza Bunge, Induces Apoptosis through Inducing Endoplasmic Reticular Stress in Human Prostate Carcinoma Cells

Abstract: 5,16-dihydrotanshinone I (DHTS) is extracted from Salvia miltiorrhiza Bunge (tanshen root) and was found to be the most effective compound of tanshen extracts against breast cancer cells in our previous studies. However, whether DHTS can induce apoptosis through an endoplasmic reticular (ER) stress pathway was examined herein. In this study, we found that DHTS significantly inhibited the proliferation of human prostate DU145 carcinoma cells and induced apoptosis. DHTS was able to induce ER stress as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…It also inhibits cell proliferation in MDA‐MB‐231 (IC 50 85.1 μM), HeLa (IC 50 27.7 μM), SiHa (IC 50 63.5 μM), and MCF‐7 (IC 50 250 μg/mL) cells. Similar inhibitory effect is also reported in DU145 and HUVECs (IC 50 1.28 μg/mL) …”
Section: The Anticancer Effects Of the Lipophilic Ingredientssupporting
confidence: 85%
See 1 more Smart Citation
“…It also inhibits cell proliferation in MDA‐MB‐231 (IC 50 85.1 μM), HeLa (IC 50 27.7 μM), SiHa (IC 50 63.5 μM), and MCF‐7 (IC 50 250 μg/mL) cells. Similar inhibitory effect is also reported in DU145 and HUVECs (IC 50 1.28 μg/mL) …”
Section: The Anticancer Effects Of the Lipophilic Ingredientssupporting
confidence: 85%
“…To cause apoptosis, DHT I decreases the Bcl‐xL level and increases the loss of Δψm and the release of cytochrome c , which activate caspase‐9, caspase‐3, and caspase‐7 . Moreover, recent study showed that DHT I induced apoptosis in DU145 cells through induction of ER as evidenced by the fact that DHT I induced apoptosis was reversed by the ER stress inhibitor salubrinal …”
Section: The Anticancer Effects Of the Lipophilic Ingredientsmentioning
confidence: 99%
“…Considering the growth inhibitory effect of the different ingredients isolated from Salvia species on tumor cell lines, the plant has become popular for anticancer evaluations. 5,16-Dihydrotanshinone I (Chuang et al, 2011), tanshinone IIA (Sung et al, 1999;Liu et al, 2012) compounds of Salvia miltiorrhiza, rosmarinic acid from Salvia fruticosa and Salvia officinalis (Xavier et al, 2009), royleanone, horminone, and acetyl horminone from the roots of S. officinalis (Slamenová et al, 2004); 6a-hydroxysalvinolone, 6a-hydroxytaxodone, aethiopinone, microstegiol, ferruginol, saprorthoquinone, 11,12-dioxoabieta-8,13-diene, taxodione, hypargenin A, hypargenin D isolated from Salvia hypargeia (Ulubelen et al, 1999;Topçu and Gören, 2007;Topcu, 2008) were effective in inhibiting proliferation and had cytotoxic activity against a panel of cell lines including human breast cancer, human lung cancer, human colon cancer, human prostate cancer and mouse lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…DHTS also significantly induced apoptosis in colorectal cancer cells, and ATF-3 might be involved in inducing apoptosis [ 4 ]. In addition, DHTS can induce apoptosis of prostate carcinoma cells via induction of endoplasmic reticular stress and/or inhibition of proteasome activity [ 5 ], and may have therapeutic potential for prostate cancer patients. In human hepatoma cells, DHTS also induced cell apoptosis through inducing reactive oxygen species (ROS) and the p38 pathway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%